A CASE OF PARTIAL CONVERGENCE: THE EUROPEANIZATION OF CENTRAL GOVERNMENT IN CENTRAL AND EASTERN EUROPE. (26th September 2014) - MEYER‐SAHLING, JAN‐HINRIK; VAN STOLK, CHRISTIAN
<x xml:space="preserve">Abstract</x> This article compares the Europeanization of central government in four Central and Eastern European countries (CEECs): Estonia, Latvia, Poland, and Slovakia. Using a large N survey of ministerial civil servants, it finds that the Europeanization of central government is characterized by partial convergence. The scope of Europeanization is large and similar among CEECs, reaching widely and deeply into government ministries. Moreover, patterns of Europeanization are similar among CEECs: the same ministries form the 'inner core' and 'outer circle' of Europeanized ministries; only a small proportion of civil servants work full‐time on EU issues and routinely engage in activities that 'project' national policies at EU level. Compared to old member states, patterns of Europeanization show signs of convergence, while the scope of Europeanization is larger in CEECs.